Permanent Pacemaker Implantation Through Persistent Left Superior Vena Cava: Safe for Normal Heart Position and Dextrocardia - Erika Maharani; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2013)
Permanent pacemaker implantation in patient with persistent left superior vena cava (LSVC) has been reported in literature. Some authors has also been reported pacemaker implantation in patient with dextrocardia. Both of this situation has a challenging situation in placing the lead in right ventricle and risks of lead dislocation. We report two cases of successful pacemakers implantation,one with mirror image dextrocardia, in patient with persistent LSVC.